COMPLICATIONS OF THROMBOLYTIC THERAPY IN ACTUAL CLINICAL PRACTICE - A. F. Sharafutdinova; M. V. Menzorov (Klinicist, 2014)
Reperfusion therapy, in particular, thrombolysis in acute myocardial infarction involves development of serious complications. This clinical situation demonstrates the complexity of treatment of patients with hemorrhagic complications after thrombolysis and makes questions on the application of antiplatelet agents and anticoagulants in such cases.